THE POTENTIAL APPLICATION OF SHARIA PRINCIPLES IN THE TOURISM SECTOR OF BATU CITY - Gautsi Hamida; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The main objective of this research is to see the potential that supports the application of sharia principles in the Batu City tourism sector. The tourism sector studied consists of hotels, restaurants and halal food, travel agencies and tourism areas. The next objective is to see the economic benefits that will be produced in the future with the application of sharia principles in the tourism sector. This study uses descriptive qualitative methods conducted by interviews, observations and questionnaires to see the response generated through a Likert scale. The results of this study indicate that parties related to the tourism sector provide a positive response to the application of sharia principles in the tourism sector, which will provide economic benefits for the industry players, the public society, and the government.Keywords: Sharia Principles, Halal Tourism, Income, Economic Benefits, Sharia TourismREFFERENCES Andriani, Dini. dkk. (2015). Kajianpengembangan wisata syariah.Laporan Akhir DeputiPenelitian danPengembangan KelembagaanKepariwisataan KementrianPariwisata2015.Arjana, I Gusti Bagus. (2015). Geografipariwisata dan ekonomi kreatif.Jakarta: Rajawali Pers.batukota.bps.go.idChookaew, S., Chanin, O., Charatarawat, J.,Sriprasert, P., & Nimpaya, S. (2015).Increasing halal tourismpotential at andaman gulf.  Journalof Economics, Business andManagement,3(7), 277-279.Crescent Rating. (2015). Muslim/halal travelmarket: basic concepts, terms anddefinitions.Singapore: CrescentRating.Dewan Syariah Nasional - Majelis UlamaIndonesia. (2016). Pedomanpenyelenggaraan pariwisataberdasarkan prinsip syariah no:108/DSN-MUI/X/2016.El-Gohary, Egypt H. (2016). Halal tourism, is itreally Halal?. Tourism ManagementPerspectives, 19(B), 124–130. https://doi.org/10.1016/j.tmp.2015.12.013Halim, Abdul. (2004). Manajemen keuangandaerah. Yogyakarta: UPP AMP YKPN.Islah, Muainul dan R. Moh. Qudsi Fauzi. (2018). Analisis pengunjung dan retribusi (pedagang) kawasan wisata religi sunan giri terhadap pendapatan asli daerah kabupaten Gresik periode 2011-2016. Jurnal Ekonomi Syariah Teori dan Terapan, 6(4), 658-671.Jonathan, Sarwono. (2006). Metodepenelitian kuantitatif dan kualitatif.Yogyakarta: Graha Ilmu.Marzuki, S.Z.S., Hall, C.M., & Ballantine, P.W.(2014). Measurement of restaurantmanagerexpectations towardhalal certification using factor and cluster analysis.ProcediaSocial andBehavioral Sciences, 121.Monroe, Myles. (2011). Purpose for living.Indonesia: Andi Publisher.Ni Lu Gede, Ana Pratiwi. (2014). Pengaruhkunjungan wisatawan, retribusiobyek daerah wisata dan phrterhadap pendapatan asli daerah(PAD) kabupaten Gianyar. E-jurnalEkonomi pembangunan, 3(3).Organisation Of Islamic Cooperation. (2017).Statistical, economic and socialresearch andtraining centre forislamic countries (SESRIC).  StrategicRoadmap For DevelopmentOf Islamic Tourism In OIC MemberCountries.Puad, Ahmad dkk.(2016). SuccessfulManagement of Shariah CompliantAccommodation SectorinMalaysia.World Applied SciencesJournal, 34(12), 1876-1881.Samori, Zakiah, et al. (2016). Review currenttrends on halal tourism: cases onselected asiancountries. Tourism Management Perspectives, 19(B), 131–136.Sugiyono. (2013). Metode penelitianpendidikan pendekatan kuantitatif,kualitatif, dan R&D.Bandung:Alfabeta.Yoeti, Oka A. (2008). Ekonomi pariwisata:industri, informasi, dan implementasi. Jakarta:Kompas.Yin, Robert K. (2014). Case Study ResearchDesign and Methods (5th ed.)Thousand Oaks CA: Sage.